2.8k views
0 votes
What is the answer to, -2x - 13 = -3x - 5​

1 Answer

2 votes

-2x - 13 = -3x - 5​

Step 1: Combine like terms

x's go with x's (-2x and -3x). To do this add 2x to both sides

(-2x + 2x) - 13 = (-3x + 2x) - 5​

(0) - 13 = (-x) - 5​

- 13 = -x - 5​

normal numbers go with normal numbers ( -13 and -5). To do this add 5 to both sides

(- 13 + 5) = -x + (- 5 +​ 5)

-8 = -x + (0)

-8 = -x

Step 2: Isolate x by dividing -1 to both sides (this will take the negative sign away from the x)


(-8)/(-1) =(-x)/(-1)

8 = x

x= 8

Hope this helped!

User Rob DiMarco
by
5.5k points